In-vitro Thermal Maps to Characterize Human Dental Enamel and Dentin - Lancaster, Paula; Brettle, David; Carmichael, Fiona; Clerehugh, Val (Frontiers in Physiology, 2017)
The crown of a human tooth has an outer layer of highly-mineralized tissue called enamel, beneath which is dentin, a less-mineralized tissue which forms the bulk of the tooth-crown and root. The composition and structure of enamel and dentin are different, resulting in different thermal properties. This gives an opportunity to characterize enamel and dentin from their thermal properties and to visually present the findings as a thermal map. The thermal properties of demineralized enamel and dentin may also be sufficiently different from sound tissue to be seen on a thermal map, underpinning future thermal assessment of caries. The primary aim of this novel study was to produce a thermal map of a sound, human tooth-slice to visually characterize enamel and dentin. The secondary aim was to map a human tooth-slice with demineralized enamel and dentin to consider future diagnostic potential of thermal maps for caries-detection. Two human slices of teeth, one sound and one demineralized from a natural carious lesion, were cooled on ice, then transferred to a hotplate at 30oC where the rewarming-sequence was captured by an infra-red thermal camera. Calculation of thermal diffusivity and thermal conductivity was undertaken, and two methods of data-processing used customized software to produce thermal maps from the thermal characteristic-time-to-relaxation and heat-exchange. The two types of thermal maps characterized enamel and dentin. In addition, sound and demineralized enamel and dentin were distinguishable within both maps. This supports thermal assessment of caries and requires further investigation on a whole tooth.